Anticandidal effect of multiple sessions of erythrosine and potassium iodide-mediated photodynamic therapy - Pran Pitaksanurat; Nirawat Mayeah; Pattranun Saithong; Surachai Phimha; Prapatsara Sirikarn; Teerasak Damrongrungruang (Journal of Oral Microbiology)
Background Erythrosine+potassium iodide-mediated photodynamic therapy has shown an anticandidal effect. Single session, however, has inadequate fungal inhibition.Objectives We aimed to examine the effects of multiple aPDT sessions on Candida albicans inhibition and singlet oxygen formation.Methods 220 μM erythrosine +/-100 mM potassium iodide was applied to C. albicans biofilms for 1 min prior to irradiation at 530±10 nm using a 250 mW/cm2 light-emitting diode. Negative and positive controls were phosphate buffer saline and nystatin, respectively. Single, double and triple irradiation sessions with a 5 min resting time between sessions were performed. Post-treatment candidal counts were done at 0, 1 6 and 24 hr while log10 colony forming unit/ml was calculated and compared using a Kruskal-Wallis with Dunn’s post hoc test at a p<0.05 - Singlet oxygen amount was compared using one-way ANOVA with a post hoc test at a p< 0.05.Results Two and three irradiation sessions to erythrosine+potassium iodide could inhibit Candida albicans at 7.92 log10CFU/ml (p < 0.001) . Singlet oxygen from a combination groups was significantly higher than for erythrosine (positive control). Moreover, the correlation coefficient (r) between singlet oxygen production and decreased Candida albicans counts was equal to 1.Conclusion Multiple sessions PDT of 220 μM erythrosine+100 mM potassium iodide effectively inhibited a Candida biofilm.